Expression and prognostic significance of MYL9 in esophageal squamous cell carcinoma - Wang, Jian-Hua (PLoS One, 2017)
OBJECTIVE: Myosin light chain 9 (MYL9) is necessary for cytoskeletal dynamics and experimental metastasis, but its expression in esophageal squamous cell carcinoma (ESCC) has not been addressed. We investigated the expression pattern and clinical significance of MYL9 in patients with ESCC. METHODS: We examined MYL9 expression using quantitative real-time PCR and western blotting in NE1 immortalized esophageal epithelial cells, ESCC cell lines, and paired ESCC tissues. MYL9 protein in 136 primary ESCC tissues and other types of solid tumor was detected using immunohistochemistry. The association between MYL9 expression and clinical parameters and survival was evaluated by statistical analysis. RESULTS: MYL9 was significantly upregulated in the ESCC cell lines as compared with NE1 cells. In the paired ESCC samples, MYL9 mRNA and protein expression was not significantly different between lesion tissues and the matched adjacent noncancerous tissues. In ESCC tissue, both intratumoral and peritumoral stroma were positive for MYL9. In the 136 ESCC samples, high MYL9 expression in the tumor cells significantly correlated with histological differentiation (p = 0.028), recurrence (p = 0.01), and vital status (p < 0.01). Patients with high MYL9 expression in the tumor cells had poorer overall survival (OS) and recurrence-free survival. Multivariate analysis revealed that high MYL9 expression in tumor cells was an independent and significant risk factor affecting OS after curative treatment (hazard ratio = 2.254, 95% confidence interval = 1.347–3.771, p = 0.002). CONCLUSIONS: MYL9 expression might be a promising prognostic marker and therapeutic target in ESCC.